Angiosarcoma arising from nasal cavity; A case report - Alisa Kimura; Makoto Yasuda; Shota Okamoto; Takahiro Tsujikawa; Shigeru Hirano (Acta Oto-Laryngologica Case Reports)
Angiosarcoma is a rare malignant tumor, even rarer particularly in the head and neck. It is considered a very aggressive neoplasm with high rates of local recurrence and a poor prognosis. We report a case of nasal angiosarcoma in which the patient underwent endoscopic surgery and postoperative chemoradiotherapy and is in good health 30 months after the treatment, without any recurrence. This result suggests that sinonasal angiosarcoma might have a better prognosis than angiosarcomas arising in other sites if it is treated appropriately. According to our review of the literature on sinonasal angiosarcomas, the 3-year overall survival rate for sinonasal angiosarcomas is 63.7%, which is better than the survival rate for angiosarcomas in other sites. Lymph node and distant metastases were rarely seen. In sinonasal angiosarcoma, appropriate resection and local control of the tumor with radiation therapy or chemoradiotherapy appear to result in a favorable outcome.